Bahasa Indonesia dalam Animasi Lagu Anak Indonesia Bersama Diva Produksi Kastari Animation - Sudaryanto Sudaryanto (Rekam : Jurnal Fotografi, Televisi, Animasi, 2018)
Indonesian Language in Lagu Anak Indonesia Bersama Diva Animation Production by Kastari Animation. Indonesian children’s songs are numerous and have their own peculiarities. One of the uniqueness of it is the utilization of verbal aspects of Indonesian language in the lyrics of the song. However, not everyone, including parents is aware of it. In the Lagu Anak Indonesia Bersama Diva with the production division of Kastari Animation, found a number of verbal aspects that are used by the songwriter. The purpose of this study is to describe the verbal aspects of Indonesian language in the lyrics of Indonesian children’s songs, especially in Lagu Anak Indonesia Bersama Diva animation. The research method used is qualitative method. The results of this study are descriptions of verbal aspects of Indonesian language including (1) rhyme, (2) onomatopoeia, and (3) toponimi used by children’s songwriters. As for the Indonesian children’s songs being researched are Naik Becak, Menanam Jagung, Tik Tik Bunyi Hujan, Burung Kakak Tua, Halo-Halo Bandung, Satu Nusa Satu Bangsa, and Bendera Merah Putih.